Species composition and geographic distribution of Fuegian Curculionidae (Coleoptera: Curculionoidea) - Posadas, Paula Elena (2012)
The objective of this paper is to provide an integrative approach to taxonomic composition and distributional information on the weevil fauna (Coleoptera: Curculionoidea) of the Tierra del Fuego archipelago. A total of 39 species belonging to 17 Curculionidae genera are recorded for the archipelago. Most of these belong to two subfamilies: Entiminae (13 species in four genera) and Cyclominae (23 species in 11 genera). Caneorhinus gravidus (Burmeister) is here established as a new junior synonym of Caneorhinus lineatus (Blanchard). The Fuegian weevil fauna is considered to represent an impoverished condition in comparison to that from continental southern South America. The Tierra del Fuego archipelago has no endemic genera of Curculionidae and only three species seem to be endemic to it (Antarctobius rugirostris Champion, Cylydrorhinus lateralis [Berg], and Cylydrorhinus fulvipes [Guérin-Méneville]). However, these three species have scarce records and more information is required to confirm their status as Fuegian endemics. No species present in Tierra del Fuego extend their distribution beyond the Andean subregion. The Fuegian weevil fauna exhibits a great linkages to that from continental southernmost South America. Synonymic lists and distributional maps are provided for each species known to occur on the islands. Identification keys and photographs of weevil taxa recorded for Tierra del Fuego are also presented.